1995
DOI: 10.1056/nejm199503093321018
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia Due to Nafamostat Mesylate

Abstract: Letters to the Editor are considered for publication (subject to editing and abridgment), provided they are submitted in duplicate, are typewritten and triple-spaced, and do not exceed 400 words of text, a maximum of five references, and one figure or table. Letters should have no more than three authors, and all should sign the letter. Please include a word count, your telephone number, and your fax number (if available).Letters should not duplicate similar material being submitted or published elsewhere, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…We found that treatment of a mouse CCD cell line with aldosterone increased the secretion of prostasin protein into culture media and that aldosterone stimulated 22 Na uptake by increasing prostasin expression. We also found that increased aldosterone levels in rats markedly increased the urinary excretion of prostasin.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…We found that treatment of a mouse CCD cell line with aldosterone increased the secretion of prostasin protein into culture media and that aldosterone stimulated 22 Na uptake by increasing prostasin expression. We also found that increased aldosterone levels in rats markedly increased the urinary excretion of prostasin.…”
Section: Introductionmentioning
confidence: 88%
“…The activities of ENaC in M-1 cells were determined by measurement of amiloride-sensitive 22 Na uptake (16). Preliminary experiments determined that amiloride-sensitive uptake of 22 Na was linear for up to 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, high efficacy of nafamostat mesilate combined with gemcitabine for pancreatic cancer has been demonstrated in animal experiments (17) that applied to clinical trials (18). Nafamostat mesilate, which is a serine-protease inhibitor (19,20), is widely used for treatment of pancreatitis (21), disseminated intravascular coagulation (22), and anticoagulation in hemodialysis (23) in Japan, and has only minimal adverse effects such as hyperkalemia or hyponatremia (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%